2011
DOI: 10.3855/jidc.1442
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure due to Brucella melitensis

Abstract: We present the case of a 42-year-old male patient who applied to the emergency department of our hospital with clinical nephritis, orchitis, acute renal failure without endocarditis, and a low-grade fever. Brucella agglutinin titers were 1:160, Rose Bengal test was positive and Brucella melitensis was isolated from urine and blood cultures.. A combination of oral rifampin (600 mg/day) and doxycycline (200 mg/day) was administered along with supportive treatment leading to resolution of his clinical status by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Comparing this case with previous studies and cases, several key similarities and differences emerge [15] , [16] . While Brucellosis-related renal complications have been documented in literature, the development of medication-induced nephrotic syndrome and toxic hepatitis following rifampin and isoniazid therapy is relatively rare [17] .…”
Section: Discussionsupporting
confidence: 62%
“…Comparing this case with previous studies and cases, several key similarities and differences emerge [15] , [16] . While Brucellosis-related renal complications have been documented in literature, the development of medication-induced nephrotic syndrome and toxic hepatitis following rifampin and isoniazid therapy is relatively rare [17] .…”
Section: Discussionsupporting
confidence: 62%
“… 24 - 25 Brucellosis is also associated with arthritis, spondylitis, epididymo-orchitis, acute renal failure, endocarditis, splenic abscess, abortion, and neurobrucellosis. 3 , 26 - 27 Childhood brucellosis produces mild to moderate disease and rarely progresses to chronicity. 28 Most pediatric reviews have reported a wide range frequencies of clinical manifestations in children with brucellosis.…”
Section: Clinical Presentation Of Brucellosis In Childrenmentioning
confidence: 99%
“…Patients commonly have a wide range of symptoms including undulant fever, headache, chills, myalgia, and arthralgia. The disease is also associated with abortion, orchitis, acute renal failure, endocarditis, splenic abscess, spondylitis, arthritis, and encephalitis [35]. Up to date, the genus Brucella includes 12 accepted nomo-species but only B. melitensis, B. abortus, B. suis , and in rare cases B. canis are considered to be human pathogens.…”
Section: Introductionmentioning
confidence: 99%